2021
DOI: 10.1016/j.heliyon.2021.e07620
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the hydrodynamic properties of the fissured layer of granitoid aquifers in the Tchologo Region (Northern Côte d'Ivoire)

Abstract: Stratiform fissured layer within basement aquifers has increasingly been tapped because of its good transmissivity and groundwater storage capacity. This study aims to determine the hydrodynamic properties and thickness of the fissured layer of granitoids in the Tchologo region where access to drinking water has deteriorated over the years. Statistical analysis of the vertical distribution of the linear discharge from 148 boreholes measured from the length below the base of the saprolites has made it possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The deduced mean discharge for the most productive part of the fractured layer is between 8 and 15.4 m 3 /h. The authors of [52] demonstrated that the mean linear discharge and mean discharge for this useful thickness were 0.13 m 3 /h/m and 5.21 m 3 /h, respectively, in the granitoid aquifers. These values are similar to those obtained by [37], who demonstrated that, for a set of 42 geological formations, the linear discharge is between 0.078 and 0.84 m 3 /h/m (average 0.38 m 3 /h/m).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The deduced mean discharge for the most productive part of the fractured layer is between 8 and 15.4 m 3 /h. The authors of [52] demonstrated that the mean linear discharge and mean discharge for this useful thickness were 0.13 m 3 /h/m and 5.21 m 3 /h, respectively, in the granitoid aquifers. These values are similar to those obtained by [37], who demonstrated that, for a set of 42 geological formations, the linear discharge is between 0.078 and 0.84 m 3 /h/m (average 0.38 m 3 /h/m).…”
Section: Discussionmentioning
confidence: 96%
“…The authors of [18] estimated it to be between 30 and 35 m on average in the Man-Danané region in Côte d'Ivoire, with the thickness of the saprolite being between 10 and 20 m (Table 9). The authors of [52] in the Tchologo region (Northern Côte d'Ivoire) also estimated it to be between 40 and 45 m (considering the slope method-see below) in granitoid aquifers. The authors of [20] demonstrated in Central India (Hyderabad, Andhra Pradesh region) in an experimental granite basin, that the fractured layer has a limited vertical thickness of 35 m on average.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of faults/discontinuities at the base of the weathering profile can also affect the hydraulic conductivity and have a major influence on the groundwater flow systems by affecting their hydraulic conductivity [36]. These fractures and fissures can also be developed by the expansion of minerals during the weathering process [39]. Depending on their form and material properties, these can be considered groundwater flow channels as conduits, barriers, or a combined conduit-barrier system and storage sites.…”
Section: Discussionmentioning
confidence: 99%
“…The second stage involved image enhancement (principal component analysis, directional filtering), aimed at better discrimination of the lineaments to be mapped. These different techniques have already been used in numerous works [27][28][29]. Principal component analysis is used to enhance images and reduce the number of bands to be processed by compressing the information according to a hierarchy [27].…”
Section: Processingmentioning
confidence: 99%
“…Once lineament mapping has been completed, it has to be validated, as satellite image processing regularly comes up along with reliability issues. Ground truth is the most reliable validation [29].…”
Section: Validation Of the Lineament Mapmentioning
confidence: 99%